A survey of the assessment and management of gout in general practitioners and medical officers within the Illawarra Network, Australia. (6th May 2016) - Terrill, Matthew; Riordan, John
Abstract: Aim: To review the assessment and management of gout by general practitioners (GPs) and medical officers (MOs) within the Illawarra Network, Australia. Method: A survey was sent to GPs and MOs within the Illawarra Network. Results: Of 110 GPs, 45 responded. Of 129 MOs, 42 responded. The overall response was 32.6%. On analysis, 65.1% felt their knowledge of gout to be adequate and 61.6% thought they had been educated well. In acute assessment, 59.1% of GPs responded that the diagnosis of gout best be confirmed with a joint aspiration and 36.4% clinical suspicion. Differing, 85.7% of MOs chose a joint aspiration. In acute management, if colchicine were used, 59.1% of GPs would give 1 mg followed by 0.5 mg an hour later, then 0.5 mg twice daily, compared to 9.5% of MOs, while 20.5% of GPs would use 1 mg twice daily. Chronic management was answered poorly. After an acute attack, urate lowering therapy (ULT) would be started 14 days after by 47.7% of GPs, compared to 69.0% of MOs. GPs were more likely to start ULT within 7 days (52.3% vs . 31.0%). With dosing of ULT, 45.3% would treat to target, while 46.5% would dose to the creatinine clearance. Prophylactic therapy with ULT would be started by 81.8%, although only 17.4% would continue it for 3–6 months. Conclusion: There is poor adherence to recommended practice for dosing of colchicine in acute gout. Also in the management of chronic gout, in particular, the timing of starting ULT and the use of prophylaxis when initiating ULT.